BUSINESS SUSTAINABILITY STRATEGY FOR MSMEs THROUGH DIGITAL MARKETING OPTIMIZATION AND PRODUCT INNOVATION - Pramesti, Hasti; Jaya, Umban Adi; Albar, Fauzan Manafi; Chrisulianti, Rizki; Wulandari, Dwiwahjuni (Transpublika Publisher, 2025)
This research aims to explore the influence of digital marketing and innovative products on the long-term success of small and medium-sized enterprises in the Greater Sukabumi region. Digital marketing is defined as an effective and efficient method of promoting products through digital channels, while product innovation focuses on developing or refining products to meet the changing needs of the market. The research method involved 35 culinary MSME players who use at least one digital marketing application, with data collection through questionnaires. The analysis of the data involved a thorough examination of validity and reliability, complemented by multiple linear regression analysis. The study's findings reveal that digital marketing significantly influences the sustainability of business operations, evidenced by a regression coefficient of 0.284. Furthermore, the research highlights that product innovation exerts an even more profound effect on business success, as indicated by a coefficient of 0.447. The F test showed that the overall regression model was significant, with an F value of 59.279 (p < 0.001). These findings are consistent with the literature showing that digital marketing adoption and product innovation are key factors in improving MSME competitiveness and performance. This study recommends improving access to technology and digital training for MSMEs, as well as collaboration with educational institutions to encourage product innovation. The limitations of this study lie in the limited number of samples and the absence of in-depth analysis of other factors that affect business continuity.